Static Penetration Resistance Test of Geotextiles According to Argentine Standards - Ricci, Luis (2025)
This paper primarily aims to provide a solution to the issue of performing the static penetration test on geotextiles, through the implementation of low-cost techniques and the adaptation of existing equipment available in laboratories or road research centers. To set the context for the reader, we will begin with a brief definition of geotextile, outline the types available on the market, describe the tests that must be carried out on these materials, and highlight the importance of the static penetration test. Finally, we will discuss in detail the adaptation of the equipment for the proper execution of the test and share the initial experiences carried out at our research center.